The Influence Of Family, Peers And Substance Availability On Substance Use Among College Students In Nigeria - Charanchi, Isah Mamman (2017)
Substance Use especially among the adolescents is a serious social problem that poses a major challenge to the World and the emerging developing communities like Nigeria. The phenomenon is hidden among people, but information regarding the nature, pattern, prevalence and psycho social correlates comes from many sources including empirical investigations. The current quantitative survey is a research enquiry relating to family (in the context of parenting styles, parental involvement), peer characteristics and their relationships on adolescent substance use in response to the dangerous and persistent trend of substance use among adolescent population in the north-west zone of Nigeria.